PENGENALAN SARANA PERKERETAAPIAN PADA SISWA DAN GURU SMPN 1 NGRAHO BOJONEGORO - Apriliani, Nurul Fitria; Prasetya, Henry Widya (Jurnal Pengabdian Kepada Masyarakat Patikala, 2023)
At this time, transportation and mobility of people in Indonesia have used many modes of rail transportation. This choice is influenced by the various advantages offered by rail transportation modes such as its large and efficient transport capacity, on time and good accessibility. Railway technology has undergone very significant developments in recent times. Starting from conventional trains, electric trains and even fast trains (High-speed Train). One of the things that influence the development of railways is the application of science and technology, one of which is science and engineering. Therefore, strengthening the basis of science and introducing technology must be carried out, including at the primary and secondary education levels as an effort to prepare quality human resources for the development of railroad technology in the future. The introduction of rolling stock to students and teachers at SMPN 1 Ngraho Bojonegoro aims to enable students and teachers to have a deeper understanding of railway technology, especially the types of railway facilities in the hope that it will become one of the tools in learning science and technology. The method used in this activity is counseling with several stages such as preparation, implementation and evaluation. The core activity is to provide a presentation regarding the development of railway technology in general, followed by an understanding of railway facilities and types of rolling stock. The results of the evaluation showed that there was an increase in knowledge and understanding regarding railways and rolling stock among the participants. The average percentage increase in understanding of grades pre-test and post-test is equal to 76.5%. In addition, 80% of respondents stated that this activity was very useful.